Analisis model z-score untuk menilai kesehatan keuangan pt permodalan nasional madani (pnm) persero - Rizky Awaliah; Yunus Tete Konde; Irwansyah Irwansyah (Faculty of Economics and Business Mulawarman University, 2016)
This study aims to determine the condition of the financial and corporate bankruptcy prediction Permodalan Nasional Madani PT Persero bankruptcy prediction model based on the Altman Z-Score. The population of this research is in the National Capital Madani PT Persero published in their official website and some more information to each other about Permodalan Nasional Madani PT Persero. The unit of analysis of this research is the company's financial statements, primarily the balance sheet and income statement of PT Permodalan Nasional Madani Limited. The sample itself is Permodalan Nasional Madani with the financial statements for 4 years in a row 2011 to 2014. It used a method of collecting the data archives with data-driven. The results showed that in 2011 the company is categorized as a company vulnerable to bankruptcy, although it has a high working capital. In 2012 it was classified as a company vulnerable areas, although it has an increased value of the Z-Score of last year. In 2013 the company under unsanitary conditions or vulnerable companies go bankrupt, with the result of reduction in working capital to total assets. And in 2014 the company also categorized as a company vulnerable to bankruptcy because the company had losses of this decline affected the global crisis in 2014. The originality of this study uses only one company as an object, PT Permodalan Nasional Madani Limited understanding of the financial health so that stakeholders can take their decisions about the company.Keyword: Altman Z-Score, Financial Health